The role of the audit oversight board: Watching the ‘Watch Dog’ - Othman, Zaleha; Shafie, Rohami; Abdul Hamid, Fathilatul Zakimi; Fadzil, Faudziah Hanim; Wan Hussin, Wan Nordin (2013)
The Audit Oversight Board (AOB) is an establishment initiated to improve audit quality. It is a patronage of the Securities Commission.It aimed to provide assurance and strengthen public confidence in the audited financial information. However, in recent years issues have been raised regarding the quality of the audited financial information.Motivated by the argument on the quality of the audited financial information, we explore the role of the Audit Oversight Board, as the auspices of the Securities Commission, to monitor the quality of the audited financial information in the Malaysian context.We adopted a generic inquiry approach to achieve our objective and employed several data gathering techniques such as interviews and documents to explore our concern.Our content analysis indicated that the AOB’s role is twofold: as a mechanism for audit governance and sustainability assurance.Our findings also revealed other important points, including improving the establishment by increasing AOB expertise, increasing its empowerment, and advancing its focus as overseer to integrative reporting.Our study contributed to literature by expanding the understanding of the Audit Oversight Board.As this is a small scale project, we suggest future research should widen the parameters of the sample scope.